Heterosis dan Heterobeltiosis Pertumbuhan dan Hasil 29 Genotipe Melon (Cucumis melo L.) - Puspitasari, Wiwit; Susilo, Edi; Togatorop, Eny Rolenti (PendIPA Journal of Science Education, 2024)
The heterosis and heterobeltiosis values ​​are genetic parameters that can be used to determine superior hybrid candidates. The heterosis value is calculated by comparing the F1 hybrid  with mid parent heterosis and best parent heterosis. This study aimed to determine the heterosis and heterobeltiosis values ​​of 29 melon genotypes. The genetic material used in the research was 29 melon genotypes. The research used a single factor Complete Randomized Block Design with three replications. The characters observed were stem diameter, leaf length, harvest age, fruit length, fruit diameter, fruit weight, fruit flesh thickness, and fruit sweetness level. Genotypes that produced high heterosis and heterobeltiosis values ​​were G29xG4 for fruit length, fruit diameter and fruit weight, G9xG4 for fruit length, fruit diameter and fruit flesh thickness, G29xG9 and G38xG4 for fruit length and fruit sweetness, G4xG38 for fruit fruit length and flesh thickness, G29xG40 for fruit weight and fruit flesh thickness, and also G40xG4 and G38xG40 for fruit weight.